Indoor Air Quality Monitoring - Ali Yeon, Md Shakaff, Prof. Dr.; Mohd. Noor, Ahmad, Prof. Dr.; A. K. M. Shafiqul, Islam; Siti Nordiyana, Md. Salim; Noor Hasyierah, Mohd Salleh (Kementerian Pengajian Tinggi Malaysia, 2010)
Prof. Dr. Mohd Noor Ahmad and his team won broze for Indoor Air Quality. IPTA R&D Expo 2005 organized by Ministry of Higher Education (MOHE) hosted by Universiti Teknologi Malaysia (UTM).